مفهوم الرّدة وموضوعات ما قيل فيها من شعر - أحمد, عدنان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يسعى هذا البحث لمحاورة مفهوم الرّدة الذي تقدمة المصادر التاريخية، وهو في محاورته لا يستند إلى المعطيات التاريخية بقدر ما يعتمد على الشعر بصفته "بنية معرفية بالإضافة إلى كه-في الوقت ذاته- بنية لغوية جمالية. وهو-أعني البحث- يبدأ بالحديث عن الرّدة في التاريخ، لينصرف بعد ذلك إلى الوقوف عند ما قيل من شعر في هذه الرّدة ؛ فيقف على أنواعه وموضوعاته، ثم يسعى للكشف عن سماته الفنية، قبل أن يخلص إلى خاتمة يبيّن من خلالها ما إذا كان هذا الشعر ينسجم مع مفهوم الرّدة كما تقدمه المصادر التاريخية، أو يختلف معه، في قليل أو كثير. This paper attempts to discuss the concept of Apostasy as presented in the historical sources. It does rely on the historical resources, but it mainly depends on poetry as an epistemological structure and, at the same time, a linguistic, aesthetic structure. This research starts by talking about Apostasy in history, and then it moves to highlight the poetry said about it, through analyzing its different types and various issues, then endeavors to uncover its artistic characteristics, before it reaches the conclusion on whether this poetry copes with, or somehow differs from APOSTASY Concept as manifested in the historical sources.